Alcohol and the public purse: Do drinkers pay their way? - Christopher Snowdon (Institute of Economic Affairs (IEA), 2015)
This study estimates the direct costs of alcohol use to the government in England, including the NHS, police, criminal justice system and welfare system. Taken together, they amount to a gross cost of 3.9 billion per annum (in 2015 prices). Revenues from alcohol taxation in England amount to 10.4 billion, leaving an annual net benefit to the government of 6.5 billion. The estimated cost of alcohol-related violent crime is nearly 1 billion per annum. Other alcohol-related crimes, including drink-driving, add a further 627 million, leaving a total cost to the police and criminal justice system of 1.6 billion. The estimated cost of alcohol-related health problems is 1.9 billion. Half of this results from alcohol-related hospital admissions (984 million). A further 530 million is due to ambulance and Accident and Emergency attendances. Welfare payments given to people who are unable to work because of mental or physical ill health problems that are attributable to alcohol consumption incur a further cost of 289 million. This study uses the most recent health, crime and drinking data to build on previous cost-of-alcohol studies. Cost-of-alcohol studies are plagued by a shortage of reliable data in several areas. This study is no exception and its estimates should be regarded as being at the top end of the plausible range. The gross cost of 3.9 billion is more likely to be an over-estimate than an under-estimate. It is important to distinguish between social and economic costs (most of which are paid by individuals and businesses) and the costs to government departments (i.e. the 'cost to the taxpayer'). Intangible costs, internal costs and societal costs are often misrepresented as being costs to taxpayers. This is the first study to have looked at the total net cost of alcohol consumption to the government in England. Our estimates suggest that the net cost of alcohol to the state is minus 6.5 billion pounds, which is to say that drinkers subsidise non-drinkers to the order of 6.5 billion pounds a year. The government could halve all forms of alcohol duty and still receive more in tax than it spends dealing with alcohol-related problems.
Keywords: 330